Phenotypic and molecular characterization of colifages from broiler farms with Colibacilosis and poultry processing plants from Azuay, Ecuador - Astudillo-Riera, Fabián; Astudillo-Vallejo, Kevin; Gómez-Asanza, Maria Laura; Pacha-Aguilar, Luis Armando; Vallecillo-Maza, Antonio Javier; Rivera-Pirela, Sergio Emiro (Revista Científica de la Facultad de Ciencias Veterinarias, 2023)
Extraintestinal pathogenic Escherichia coli, termed E. coli avian pathogenic possess specific virulence attributes causing invasive infections in poultry, namely Colibacillosis. Veterinarians have limited options of antimicrobial agents for its treatment, due to problems of bacterial resistance of E. coli that indirectly affects human health. As an alternative, the use of bacteriophages with specific bacteriolytic power against enteropathogenic bacteria is proposed. The objective of this study was to characterize lytic bacteriophages specific for E. coli (coliphages) as a biocontrol alternative against avian Colibacillosis, determining their specificity against enteropathogenic E. coli isolated from the area, their lytic capacity, phenotype and genotype. For this, semi-solid environmental samples were collected from poultry slaughterhouses and from wastewater in production farms. With the samples, it was proceeded to isolate the plaques formed by the bacteriophages with the best apparent lytic activity against E. coli TOP10F’ and on the previously characterized pathogenic E. coli isolates. A total of 36 coliphage isolates were tested against 10 pathogenic strains of E. coli. Of these, 22 phages affected between 10–50 % of the strains evaluated, 5 phages infected between 60 and 70 % and only 9 phages did not show lytic capacity against pathogenic E. coli strains. The phages with the highest lytic capacity were selected and genotypically characterized by the Restriction Fragment Length Polymorphism (RFLP) technique, after treatment with restriction enzymes: BamHI, EcoRI, EcoRV and Hind III. As a result, 4 coliphages with different band patterns were obtained. It is concluded that a wide variety of coliphages with lytic potential for the biocontrol of pathogenic E. coli can be isolated from environmental samples of poultry farms diagnosed with Colibacillosis.